Intoxicações por agrotóxicos registradas em sistema de notificação e centros de informações toxicológicas brasileiros: uma revisão integrativa - Silva, Yasmin Rebeca Araujo (Brasil, 2023)
The increasing use of pesticides in the country contributes to the cases of poisoning and reaffirms the need for more effective public policies of control. This paper aimed to analyze the main scientific evidence on the profile of patients seen by the Brazilian Toxicological Information Centers - CIT and notifications of the Sistema de Informação de Agravos de Notificação - SINAN, with intoxication associated with the use of pesticides in urban and rural areas, between January 2018 and January 2023. An integrative literature review was carried out, encompassing studies with qualitative and descriptive methods, in order to identify publications relevant to the theme. As a result of the search, the predominant profile found was that of adult men, urban residents, in single acute events, exposed in their own home by agricultural pesticides, through the digestive tract, and as the main circumstance the attempt of self-extermination. Studies such as this, which determine the epidemiological profiles allow the basis for the creation of specific health planning for the population.